Role of substrate bias during deposition of magnetron sputtered Ni, Ti and Ni–Ti thin films. (October 2013) - Priyadarshini, B G; Kumar Gupta, M; Ghosh, S; Chakraborty, M; Aich, S
Abstract : The present work aims to know how cosputtered Nix Ti1−x thin films differ from pure Ni and pure Ti thin film. Ni thin films exhibited <111> texture irrespective of substrate bias voltage, while film surface roughness as revealed by atomic force microscopy was sensitive to biasing. The negative substrate bias voltage induced a change in preferential orientation of Ti thin films. On the other hand, Ni–Ti thin films exhibited amorphous nature irrespective of substrate bias voltage. The stability of the crystal structure of pure Ni, pure Ti films and that of amorphous structure of Nix Ti1−x films under high ion bombardment could be predicted by classical molecular dynamics based on embedded atom method potential.